2016
DOI: 10.1055/s-0042-115565
|View full text |Cite
|
Sign up to set email alerts
|

Expectations for Endoscopic Training During Gynaecological Specialty Training – Results of a Germany-wide Survey

Abstract: Endoscopy is an integral part of surgical gynaecology and is playing an increasingly important role in ensuring adequate gynaecological training in the context of specialty training in general. At present, little is known about the expectations and notions of young junior doctors with respect to endoscopic training. For this reason, junior doctors throughout Germany were surveyed on this topic and asked to share their opinions. Methods: Using an anonymized standardized survey, the following information was eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…Notably, international gynecological (oncology) trainees have emphasized the importance of hands-on surgical skills, particularly for complex surgeries and laparoscopies [ 4 , 11 , 12 ]. Our survey supports this view, as trainees reported a preferred minimum of >30 performed laparoscopic surgeries, which is in line with the previous reports [ 8 ]. Only half of the trainees in this cohort reported receiving explicit support for their surgical training, highlighting a significant lack of structured educational guidance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Notably, international gynecological (oncology) trainees have emphasized the importance of hands-on surgical skills, particularly for complex surgeries and laparoscopies [ 4 , 11 , 12 ]. Our survey supports this view, as trainees reported a preferred minimum of >30 performed laparoscopic surgeries, which is in line with the previous reports [ 8 ]. Only half of the trainees in this cohort reported receiving explicit support for their surgical training, highlighting a significant lack of structured educational guidance.…”
Section: Discussionsupporting
confidence: 92%
“…A recent survey of German OBGYN residents revealed a high value placed on learning laparoscopic surgical techniques [ 8 ]. However, our study showed that the quality of surgical training in OBGYN was only rated as satisfactory to sufficient, with trainers giving an average rating of 2.7 and trainees giving a rating of 3.7 on a scale from 1 to 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016 Gabriel et al [34] surveyed 109 resident junior doctors on laparoscopic training within specialist training in Germany. 87% of respondents consider learning minimally invasive techniques to be very important.…”
Section: Medical Specialty Trainingmentioning
confidence: 99%
“…Die Strukturen der Arbeitsgemeinschaft für Gynäkologische Endoskopie (AGE) der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe e. V. (DGGG) in Bezug zu Aus-und Fortbildung haben zu einer breiten Akzeptanz geführt [1,2]. Erfreulicherweise haben sich sowohl die Assistenzärzte, die jungen Fachärzte als auch die erfahrenen gynäkologischen Operateure durch dieses Ausbildungskonzept angesprochen gefühlt [3]. Zu einer weiten Verbreitung haben sicherlich die Zusammenarbeit mit dem Forum Operative Gynäkologie [4], die zunehmende Anerkennung der AGE durch die DGGG [5] und der Einbau von modernen Übungstechniken [6]…”
unclassified